On the Use of Adjoint-Based Sensitivity Estimates to Control Local Mesh Refinement (Communications in Computational Physics, 2010)
The goal of efficient and robust error control, through local mesh adaptationin the computational solution of partial differential equations, is predicated on theability to identify in an a posteriori way those localized regions whose refinement willlead to the most significant reductions in the error. The development of a posteriori errorestimation schemes and of a refinement infrastructure both facilitate this goal, howeverthey are incomplete in the sense that they do not provide an answer as to where themaximal impact of refinement may be gained or what type of refinement — elementalpartitioning (h-refinement) or polynomial enrichment (p-refinement) — will best leadto that gain. In essence, one also requires knowledge of the sensitivity of the error toboth the location and the type of refinement. In this communication we propose theuse of adjoint-based sensitivity analysis to discriminate both where and how to refine.We present both an adjoint-based and an algebraic perspective on defining and usingsensitivities, and then demonstrate through several one-dimensional model problemexperiments the feasibility and benefits of our approach.